PENGUKURAN EFISIENSI WAKTU KERJA DENGAN JAM HENTI OPERASIONAL PENCUCIAN MOBIL ROBOTIC OTOBILAZ CAR WASH AND DETAILING - Hauzan Abbad Muzakki; Raffary Aqilla, Muhamad Rifqi, Paduloh (Jurnal Ekonomi dan Bisnis, 2025)
Steam Autobilaz Car Wash & Detailing is located at Jl. Cemara Raya, Jakasampurna, District. West Bekasi, is a company engaged in car washing services with the main service of cleaning cars using robotic steam technology. Robotic car wash is a modern car wash concept with advanced technology. An automated system that uses robots to clean vehicles. Employee activities and performance in the operational process of car washing using steam robot technology greatly influence the time required to manufacture a product or perform a service. In operating the car wash at Steam Otobilaz, it was found that the working time required to wash each car was not optimal. This can be seen from the uncertainty of time in the cleaning process which causes an increase in service time per car and results in a decrease in labor efficiency. So the aim of this research is to study how to calculate standard time based on stopwatch time (stopwatch time study) in the Robotic Car Wash business. The author conducted standard time research directly using the Stop Clock method and to find out how long it takes to complete one manufacturing cycle in Robotic Car Wash operations. Stopwatches are included in the category of working time measurement methods that are directly applied to short, repetitive work. Based on this method, standard time is obtained to increase the efficiency and effectiveness of operational processes. The analysis results show that robot car wash technology is able to reduce operational duration significantly with a standard time of 26.67 minutes, this could be a proposed improvement for the company.